Metal(loid)s in Bottom Sediments Ecological and Human Health Risk Assessment - Tytła Malwina; Pohl Alina; Kernert Joanna (Architecture, Civil Engineering, Environment)
The research aimed to assess the ecological and health risks of selected metal(loid)s (Cd, Cr, Cu, Ni, Pb, Zn, and As) in the bottom sediments of four water reservoirs located in various regions of Poland (Central Europe). The results of the ecological assessment indicate that Cd is the primary element posing a risk among analyzed metal(loid)s. Health risks assessment revealed that the analyzed elements enter the human body mainly through ingestion. Moreover, both from a non-carcinogenic and carcinogenic perspective, children are more exposed to the negative impact of these elements. Although the obtained result indicates that carcinogenic risk is acceptable, appropriate actions should still be taken to prevent the possible negative effects of metal(loid)s in the analyzed bottom sediments, particularly regarding Cd, Cr, Ni, and As.